4-Ethyl-5-(2-hydroxyphenyl)-2H-1,2,4-triazole-3(4H)-thione - Dege, N; Özdemir, N; Çetin, A; Cansiz, A; Sekerci, M; Dinçer, M (Int Union Crystallography, 2005)
In the title compound, C10H11N3OS, an intramolecular C-H...S hydrogen bond is observed, which leads to a thione tautomer in the solid state. The benzene ring forms a dihedral angle of 85.33 (6)degrees with the triazole ring. There are intermolecular N-H...S and O-H...N hydrogen bonds and C-H...pi interactions.